Conceptual framework for lightweight ciphertext policy-attribute based encryption scheme for internet of things devices / Norhidayah Muhammad and Jasni Mohamad Zain - Muhammad, Norhidayah; Mohamad Zain, Jasni (Penerbit UiTM, 2019)
The purpose of this paper is to propose a conceptual model for data security in the Internet of thing devices. Estimated by Jumoki in early 2018 to 2022, there will be about 18 billion connected Io devices. Therefore many issue related to IoT devices were discussed especially data security. Cryptography with lightweight features is one of the focus area by researchers to develop a powerful cryptography scheme for IoT devices. Lightweight cryptography scheme has been discussed and proposed widely recently. There are AES, PRESENT, Hash algorithm declared as a lightweight algorithm under consideration in ISO/IEC 29192 “Lightweight Cryptography”. Unfortunately these lightweight algorithm is one-to-one communication cryptography technique. This algorithm is very practical to implement for individuals or for small group communication but unpractical when implemented in a big company where many users can become a bottleneck. Therefore we propose a lightweight Ciphertext Policy-Attribute Based Encryption (CP-ABE) algorithm to implement in IoT devices. CP-ABE algorithm is one-to-many technique suitable for secure grouping communication, but this algorithm is not a lightweight feature. Therefore this paper proposes a lightweight CP-ABE algorithm for IoT devices.